Evaluasi Pemanfaatan Dana Desa untuk Ketahanan Pangan Kampung Fonatu, Kabupaten Maybrat - Lili Sarce Joi Sapari; Edward Clan; Vera Fonia Kocu (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
The purpose of this study was to evaluate the food security program in North Aifat Village, Maybrat Regency. The analysis technique used was qualitative descriptive, using the theory of Miles and Huberman, with 5 informants. The results obtained were that the most potential supporting factor in the food security program was the availability of large land in each family so that it could produce large-scale harvests. Another supporting factor was that the community already had basic knowledge related to agriculture. The constraints faced by recipients of the food strengthening program in North Aifat Village were the lack of continuous assistance, then for pineapple and dragon fruit farming businesses the constraints were the availability and use of fertilizers and overcoming pests. While for catfish and chicken farming the constraints faced were feed and marketing media.